Impacts of invasive mechanical ventilation on patients from COVID-19: integrative review (Research, Society and Development, 2021)
The use of invasive mechanical ventilation (IMV) has become an important alternative for critically ill patients due to COVID-19, as this therapy provides those assisted in hospital admissions with the necessary oxygen, reducing mortality in healthcare units. Thus, the present study aimed to describe the impacts of invasive mechanical ventilation on patients victims of COVID-19. Searches were carried out in the electronic journals Lilacs, PubMed, Scopus and MedLine. Using the guiding question: What are the repercussions of invasive mechanical ventilation in the treatment of patients with COVID-19? As a result, it indicated that there is often an increase in the chances of death in those affected, as well as the misuse of IMV can also complicate the recommended therapeutic treatment. Therefore, the common impacts on patients victims of COVID-19 under invasive mechanical ventilation result in lung injury or worsening of the patient's clinical conditions, such as the appearance of barotrauma, atelectasis, causing insufficient pressure during ventilatory support.